The role of preference formation and perception in unequal representation: Combined evidence from elite interviews and focus groups in Germany - Florian Fastenrath; Paul Marx (University of Duisburg-Essen, Institute for Socio-Economics (ifso), 2023)
Unequal representation can result from politicians' biased perception of public opinion. Existing research has focused on the numerical accuracy with which politicians estimate preferences distributions in surveys. This method ignores politicians' broader assumptions about public preferences; e.g. regarding their crystallization, salience, malleability, and measurability in surveys. We address these assumptions in a novel two-stage research design using redistributive tax policy in Germany as a case. Interviews with parliamentarians show that voters are perceived as uninformed, disinterested, and susceptible to anti-tax mobilization by business representatives. Support for taxing the rich in polls is dismissed as superficial and irrelevant for political behavior. In a second step, we verify these assumptions in twelve focus groups with high- or low-skilled citizens. They largely confirm the assumed indifference and anti-tax attitudes. A class gap in tax preferences cannot be identified. Support expressed in previous surveys tends to disappear in conversations, which aligns with politicians' experiences.
Keywords: 330